2019
DOI: 10.1101/693887
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Juxta-membrane S-acylation of plant receptor-like kinases – fortuitous or functional?

Abstract: S-acylation is a common post-translational modification of membrane protein cysteine residues with many regulatory roles. S-acylation adjacent to transmembrane domains has been described in the literature as affecting diverse protein properties including turnover, trafficking and microdomain partitioning. However, all of these data are derived from mammalian and yeast systems. Here we examine the role of S-acylation adjacent to the transmembrane domain of the plant pathogen perceiving receptor-like kinase FLS2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 47 publications
1
4
0
Order By: Relevance
“…These data demonstrate that, in common with other post-translational modifications, S-acylation may affect multiple sites within an RK with differing effects on RK function (e.g. this work and [25]). The position and effect of the S-acylation site identified here at the C-terminus of the FLS2 and EFR kinase domains is highly conserved amongst plant RKs, and is also found in the closely related receptor-like cytoplasmic kinases (RLCKs) that act downstream of activated RKs.…”
Section: Fls2 Kinase Domain S-acylation Is Required For Late Immune R...supporting
confidence: 60%
See 1 more Smart Citation
“…These data demonstrate that, in common with other post-translational modifications, S-acylation may affect multiple sites within an RK with differing effects on RK function (e.g. this work and [25]). The position and effect of the S-acylation site identified here at the C-terminus of the FLS2 and EFR kinase domains is highly conserved amongst plant RKs, and is also found in the closely related receptor-like cytoplasmic kinases (RLCKs) that act downstream of activated RKs.…”
Section: Fls2 Kinase Domain S-acylation Is Required For Late Immune R...supporting
confidence: 60%
“…Altogether, our observations indicate that FLS2 S-acylation stabilises FLS2-BAK1 association and maintains FLS2 in an signalling competent state at the plasma membrane. Discussion FLS2, a prototypical RK, has been previously shown to be S-acylated at a pair of juxtatransmembrane domain cysteines (Cys 830,831), but S-acylation at these sites is apparently dispensable for function [25]. Here we demonstrate that FLS2 is S-acylated at additional cysteine residues (Cys 1132,1135) in a ligand-responsive manner and that this is required for efficient flg22-triggered signalling and resistance to P. syringae DC3000 bacterial infection.…”
Section: Fls2 Kinase Domain S-acylation Is Required For Late Immune R...mentioning
confidence: 99%
“…Initial work on receptor-like kinases suggested that Sacylation at juxta-TM cysteines had a mild positive effect on signalling outputs from the Arabidopsis FLS2 (flagellin sensing 2) flagellin receptor [4], however, recent work indicates that this is likely artefactual due to the use of epitope tags that confound FLS2 function [36] and the use of overexpression constructs. A recent reappraisal of these data using untagged FLS2 constructs driven by the native promoter and expressed at wild type levels indicates that juxta-membrane S-acylation of FLS2 is entirely dispensable for function [37]. This unexpected finding prompted a bioinformatics based assessment of juxta-membrane S-acylation in receptor-like kinases across species.…”
Section: Recent Insights Into S-acylation In Plantsmentioning
confidence: 99%
“…Interestingly, following on from investigating juxta-TM S-acylation, this study also found that even when juxta-TM S-acylation was abolished both Erecta and FLS2 remained S-acylated, albeit at lower levels. Testing of a range of other receptor-like kinases that naturally lack juxta-TM sites indicated that they were also S-acylated and suggests that receptorlike kinases have additional S-acylation sites [37]. The location and function of these sites is currently unknown.…”
Section: Recent Insights Into S-acylation In Plantsmentioning
confidence: 99%
See 1 more Smart Citation